Effect of rotation speed and steam pressure on physico-chemical properties of drum dried pitaya (Hylocereus polyrhizus) peel - Chia, Siew Lian; Chong, Gun Hean (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Red pitaya (Hylocereus polyrhizus) peel is a rich source of fibre, antioxidant and betacyanin; however, it is discarded during processing, so it is able to cause environmental problems. In order to convert the fruit waste to potential by-product ingredients, drum drying is used as pre-treatment to create an ingredient which is shelf-stable. In this study, the effects of rotation speed and steam pressure of drums on the physico-chemical properties of pitaya peel that had undergone drum drying are investigated. Pitaya peel was dried in a laboratory scale double drum dryer at rotation speed of 1, 2, and 3 rpm at steam pressure of 1, 2, and 3 bar. The drum dried pitaya peel was then further analyzed based on percentage yield, moisture content, water activity, betacyanin retention and color change. Interaction of steam pressure and rotation speed gives significant effect (p < 0.05) on percentage yield, moisture content, water activity, betacyanin retention and Hunter L value, whereas it has no significant on Hunter a and b values. The best combination parameters (1 rpm and 2 bar) yield the highest betacyanin retention (80.21 mg/g of dry solid), acceptable moisture content (10.66% wet basis), water activity (aw = 0.42) and with 7.61% of yield.